Bloqueta de concreto con incorporación de fibra de acero de neumático reciclado en Juliaca, Puno - Parizaca, Jhon (2024)
The objective of this research work carried out in the department of Puno is to analyze the concrete block with the incorporation of recycled tire steel, which is why it was analyzed in proportions of 0%, 3%, 5% and 7%. Rural homes in the department of Puno, according to the INEI, are mostly made with concrete and adobe blocks; on the other hand, disused tires contaminate the environment due to the inappropriate use they were given for many years. That is why this research aims to improve the mechanical resistance of the blocks without generating an additional cost with the use of steel fibers from recycled tires. Finally, we conclude that the incorporation of tire steel fiber positively influences the mechanical properties of the blocks, managing to increase their resistance by 14.90% compared to the standard sample and in a proportion of 7% incorporation of tire steel fiber. Likewise, the use of steel fiber in tires reduces the damage it causes to the environment.